Context-aware reminder for food journal mobile application - Hoe, Chia Yong (2020)
Most of the existing food journal apps in the market provide reminder functionality to notify users for logging a meal at specific mealtime each day. Yet, all these time-based reminders are not sophisticated enough because the users presently scheduling a reminder may not be able to predict a specific time. Since contextawareness in mobile computing is concerned with gathering information about the user current situation, this project proposes to develop a context-aware reminder for food journal mobile application, that utilises factors of time, device location, and user activity recognition to notify the users in a more efficient way. Provided the user has set the context-aware reminder at certain time interval, for instance 2 - 3 pm for Lunch. At 2 pm, the app will start tracking user device location using Fused Location Provider API. If the user is detected inside a restaurant circular region of specified radius for certain period, the app starts tracking step counter sensors value for activity recognition purposes. Then, if the user current step counter remains the same and still stay inside the restaurant region for certain period, the app assumes user is sitting for a meal in a restaurant within specific mealtime. The app then vibrates the device and shows a notification, which will prompt user for logging the meal he is taking. This project also showed the phone battery consumption when user device is receiving location updates using Fused Location Provider API, and tracking step counter sensor value is such simple yet effective way to detect sitting activity.